(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Companies are discovering possibilities to use their cash in the most strategic manner as aresult of the adoption of required Corporate Social Responsibilities (CSR) law. [CSR] stands forCorporate Social Responsibilities. In this particular setting, the article makes an attempt to assess thebenefits provided by large corporate foundations. The purpose of this article is to investigate the potentialfor small and medium-sized businesses (commonly known as SMEs) to play a major role in the field ofcorporate social responsibility. In this particular setting, it also focuses on the challenges faced by nongovernmentalorganisations as well as the opportunities they provide (NGOs).